Strategic Investments in Mandalika: A Human Rights and Sustainable Tourism Approach - Ahmad Saifuddin Bukhari; Alwafi Ridho Subarkah (Sospol, 2026)
Tourism development promoted through Indonesia’s National Strategic Projects (Proyek Strategis Nasional, PSN) has long been regarded as a key engine for national economic growth. Yet, large-scale investment initiatives of this kind often bring complex social consequences, particularly for local communities whose land and livelihoods are directly affected. While much of the existing research has centred on the economic and infrastructural achievements of these projects, relatively little attention has been given to their human rights dimensions. This study seeks to address that gap by exploring how PSN investment in tourism affects human rights, with a specific focus on the Mandalika Special Economic Zone (SEZ) in West Nusa Tenggara. Using a qualitative approach, the research draws on an extensive review of literature, policy documents, reports, and media coverage. Thematic analysis was applied to identify recurring patterns and to interpret how the Mandalika SEZ reflects broader issues of justice, inclusion, and sustainability in Indonesia’s development agenda. The findings reveal that, under the name of PSN, the development of Mandalika SEZ has involved serious human rights concerns, including land dispossession, disruption of livelihoods, and intimidation during land acquisition processes. These findings illustrate the ongoing tension between rapid economic expansion and the protection of human rights. The study concludes that truly sustainable and inclusive tourism requires transparent land management, fair compensation, and continuous dialogue among all stakeholders to ensure that progress does not come at the expense of community rights.